1974
DOI: 10.1002/cpt1974153276
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein binding of diphenylhydantoin Effects of sex hormones, renal and hepatic disease

Abstract: The in vitro binding of diphenylhydantoin (DPH) to the lJrotein in plasma from 97 volunteers has been studied using ultrafiltration at 37° C. The capacity of plasma protein to bind DPH did not ditfer significantly between pregnant women (11.6 ± 1.7% of total drug unbound), women taking oral contraceptives (9.9 ± 1.7% unbound), healthy males (10.6 ± 1.3% unbound), and healthy females (11.0 ± 3.2% unbound). However, in plasma trom patients with renal disease (15.8 ± 3.9% unbound), hepatic disease (15.9 ± 6.0%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
0
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(46 citation statements)
references
References 6 publications
6
39
0
1
Order By: Relevance
“…Although VPA is highly bound to plasma proteins, binding varies to a certain degree, ranging from 87.7 to 94.8% in the group of healthy subjects studied here, this variation being in the same magnitude as found with phenytoin (Hooper et al, 1974). Thus, a twofold variation in the unbound fraction in plasma can be observed.…”
Section: Disussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although VPA is highly bound to plasma proteins, binding varies to a certain degree, ranging from 87.7 to 94.8% in the group of healthy subjects studied here, this variation being in the same magnitude as found with phenytoin (Hooper et al, 1974). Thus, a twofold variation in the unbound fraction in plasma can be observed.…”
Section: Disussionsupporting
confidence: 54%
“…Preliminary data indicate plasma protein binding of VPA to be in the magnitude of another antiepileptic drug, phenytoin, 90% of which is normally protein bound (Potratz & Schulz, 1976). No information is available, however, on the binding of VPA in disease states such as renal failure or hepatic disease, which have been described to be associated with reduced binding of phenytoin (Reidenberg, Odar-Cederlof, von Bahr, Borga & Sjoqvist, 1971;Hooper, Bochner, Eadie & Tyrer, 1974). Alterations in protein binding may be of considerable importance, since they can profoundly affect the pharmacokinetics of drugs (Schoenemann, Yesair, Coffey & Bullock, 1973;Gugler, Shoeman, Huffman, Cohlmia & Azarnoff, 1975).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Early studies suggested that the inter-subject variability in degree of protein binding of phenytoin may be considerable and that the free phenytoin concentration might be better correlated with clinical toxicity (Booker & Darcey, 1973;Hooper et al, 1974;Bochner et al, 1974). The latest study of phenytoin binding (Peterson et al, 1983) has reopened the controversy as to the degree of interindividual variation in binding in otherwise healthy epileptic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The various investigations have been summarised by Porter & Layzer (1975) and Loscher (1979). In vitro techniques have also been used to assess the effects of factors such as age, pregnancy, renal and liver disease on the plasma protein binding of the drug (Reidenberg et al, 1971;Hooper et al, 1974;Bender et al, 1975;Hayes et al, 1975). However, relatively little work appears to have been done studying the binding of phenytoin to Monks et al, 1978).…”
Section: Introductionmentioning
confidence: 99%